CONSIDERAÇÕES SOBRE AUTISMO E DIREITO AO TRABALHO: SOCIABILIDADE E IDENTIDADE SOB A ÓTICA DOS DIREITOS HUMANOS (Reflection and Critique Law Magazine, 2020)
The purpose of the article is to investigate the legal provisions that guarantee access to the labor market for people with Autistic Spectrum Disorder (ASD) from the perspective of humans rights. Despite of the existence of a vast legislative production that affirms the labor right and public policies about the subject, prejudice is still being a relevant factor in the life of those who lives with ASD. Therefore, law nº. 8.213 / 1991 appears as an integration device between the disabled person and the job market. The methodology used in this article was documentary and bibliographic research. The structure is divided as follows: first was analyzed the models of medical and social disability, followed by the history of the fight for the rights of people with disabilities, after was evaluated the relationship between the social and medical model and ASD, ending with the investigation of legislation and public policies that link work to autistic people. It can be concluded that the history of the legislation that contemplates the person with ASD, it was also noticed that the law was not accompanied by resources and structures for its implementation. It was possible to notice that most of the Brazilian legislation is tied to the medical concept of disability, which makes it difficult for people with ASD to access public inclusion policies.